Association of HLA-DRB1 with Recurrent Aphthous Stomatitis in Northeast Iranian Population - Nooshin Mohtasham; Hooshang Rafatpanah; Atessa Pakfetrat; Reza Zare; Hamideh Kade; Mahshad Hosseini shad; Maryam Zamanzadeh; Farnaz Mohajertehran (Reviews in Clinical Medicine, 2020)
Introduction:Recurrent aphthous ulcers are the most common pathologic conditions of the oral cavity, which despite having clear clinical features, the etiology is unknown. This study aimed to determine the relationship between one of the histocompatibility antigens (HLA DRB1) and its sub-groups with the incidence of recurrent aphthous ulcers in an Iranian population (North East of Iran). Methods: In this case-control study, a total of 72 patients with recurrent aphthous ulcers and 70 healthy subjects in Northeast Iranian population were included. Genotyping was done by polymerase chain reaction-specific sequence primers (PCR- SSP) for each sample, according to standard kit protocol (BAG- Germany). Results: In 72 patients with recurrent aphthous ulcers that were included in this study, 26 were male and 46 were female; of the 70 control patients, this difference not significant statistically (P>0.05). The frequency of HLA -DRB1 *16 was 0.7% in the healthy subjects, however frequency of HLA -DRB1 *16 in patients with recurrent aphthous stomatitis (RAS) was 42.36%, and this difference was statistically significant (P=0.03). But, this difference was not observed in other subgroups.Conclusion: The frequency of DRB1 * 16 in the patients with RAS were higher than the group. Therefore, DRB1 * 16 can be suggested as a Predisposing factor for aphthous ulcers patients.